Modelling and optimization of a hybrid photovoltaic-parabolic trough concentrated solar power plant: Technical, economic, and environmental - Montaser Mahmoud; Salah Haridy; Ayman Mdallal; Abdul Hai Alami; Mohammad Ali Abdelkareem; Abdul Ghani Olabi (Energy Nexus)
This research presents detailed guidelines for modeling and optimizing an integrated photovoltaic-concentrated solar power (PV-CSP) plant using response surface methodology (RSM), tailored to the climate of Sharjah, UAE. Five factors are considered in the optimization, which are the percentage share of PV/CSP (A), PV tilt angle (B), PV spacing (C), CSP solar multiple (D), and thermal storage size (E), with corresponding ranges of 10–90% (equivalent to 10 to 90 MW), 20–40°, 1–7 m, 2.5–7.5, and 5–20 h, respectively. The research utilizes three software tools: System Advisor Model (SAM) for CSP, PVsyst for PV, and Design-Expert for RSM. Based on the analysis of variance (ANOVA), seven factors (A, C, E, D², AC, AE, and DE) are significant for energy output, while eight (A, C, D, E, AC, AD, AE, and DE) are significant for LCOE. Through multi-objective optimization aimed at maximizing energy production while minimizing LCOE and land area, the results indicate that the optimal configuration comprises 38.6% CSP and 61.4% PV. This configuration achieves an energy output of 3.64 × 108 kWh/year, a LCOE of $0.033/kWh, and a land area of 743.46 acres. These results were achieved with B, C, D, and E of 27.18°, 5.45 m, 4.41, and 15.49 h, respectively.